(untitled) (The Research of Medical Science Review, 2025)
Background: Dental implants have revolutionized the restoration of oral function and aesthetics in edentulous patients. Despite high success rates, the incidence of implant failure remains a significant clinical concern, largely due to both mechanical and biological complications. Objective: This literature review explores the multifactorial etiology of dental implant failures, focusing on surgical, patient-related, prosthetic, and systemic risk factors. Special attention is given to peri-implantitis, biomechanical stress, and bruxism, systemic health conditions such as diabetes and osteoporosis, and lifestyle habits including smoking. Methodology: This review was conducted by analyzing recent peer-reviewed studies focusing on biological, mechanical, systemic, and surgical risk factors contributing to dental implant failure. Conclusion: The findings highlight the need for individualized treatment planning and risk mitigation to improve the long-term success and stability of dental implants.